Modeling of vertical ground heat exchangers in the presence of groundwater flow and underground temperature gradient - Iosif-Stylianou, Iosifina; Tassou, Savvas A.; Christodoulides, Paul; Aresti, Lazaros; Florides, Georgios A. (My University, 2019)
The paper focuses on the methodology for modeling the thermal response of vertical Ground Heat Exchangers (GHEs), when imposing underground water flow and a temperature gradient on the numerical model to represent the temperature of the depth profile. Four underground layers with different properties were studied, in order to identify their contribution in the total response of the GHE. In more detail, vertical GHEs in water saturated and dry soils, with or without water flow, are modeled with the equations that govern the heat transfer being presented. The numerical solution of the equations is based on the Finite Element Method (FEM) with boundary values. The model is validated with actual data of a Thermal Response Test (TRT) carried out in Lakatameia, Cyprus. Using the validated model, the heat injection rate of a GHE is investigated by determining the effect of the (a) summer and winter mode of operation, (b) underground temperature variation in depths smaller than 7 m due to daily and seasonal changes, (c) borehole radius, (d) borehole grout properties, (e) U-tube diameter, (f) U-tube leg and borehole centers distance, and (g) groundwater flow velocity.
Keywords: Computational modeling; Geothermal energy; Ground heat exchangers; Groundwater flow